KONSEP TAZKIYATUN NAFS DALAM TASAWUF SEBAGAI UPAYA PEMBENTUKAN AKHLAK MULIA - Fiona Eka Putri (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
Sufism is a branch of Islamic scholarship that emphasizes the development of the spiritual dimension and purification of the human soul. The core concept in Sufism is tazkiyatun nafs, which refers to the process of purifying the human soul from despicable traits to a state of tranquility and closeness to Allah. This study aims to examine the concept of tazkiyatun nafs in the Sufi tradition and its implications for the formation of noble character. The method used is library research by examining various sources from books, classical works by Sufis and scientific journals discussing the dimensions of ethics and Sufism. The results of the study show that tazkiyatun nafs has a strong relevance in shaping noble character because it integrates the spiritual, moral, and social dimensions of human beings.